Cost Development and Cost Drivers in UK Offshore Wind Farms - Sindre Lorentzen; Petter Osmundsen (Wind Energy)
ABSTRACT The offshore wind industry faces challenges of impairments, project abandonment, and no bids in auction rounds, following several years of cost increases and project delays. Both industry and government rely on cost reductions. Companies struggle with low business‐economic profitability, and taxpayers require a justification for government subsidies. At the same time, consumers and industry are concerned with high electricity prices. Industrialization and learning effects in the supply chain could potentially represent a path forward, as they have proven to be in the onshore wind industry. In the context of capacity unit costs (CAPEX/MW) of UK bottom‐fixed offshore wind farms, we study the prevalence of various drivers of cost developments: technological innovation, economies of scale, learning curves, and trends in cost drivers such as water depth and distance to shore. Compared with previous studies, we use a substantially larger dataset and investigate the drivers of cost development jointly. Our dataset consists of 39 wind farms commissioned between 2000 and 2023. Results show that both economies of scale and technological innovation tend to reduce costs. Nevertheless, the cost‐increasing effect of new wind farms being situated farther offshore and in deeper waters has dominated and thus increased the overall cost level—an 8.4% cost increase per doubling of installed capacity. The conditional learning rate is found to be −21%. An explanation for this “anti‐learning” could be a short‐run trade‐off between learning and technological innovation.